UPAYA PENINGKATAN KETERAMPILAN IBU BALITA DALAM PENATALAKSANAAN ISPA/ PNEUMONIA DI RUMAH DENGAN MENGGUNAKAN MEDIA KARTU BACA MTBS DI WILAYAH KERJA PUSKESMAS BELIMBING KOTA PADANG - Tisnawati Tisnawati; Murniati Muchtar (Ensiklopedia of Journal, 2020)
Death of ARI sufferers in infants occurs when the disease has reached a degree of severe pneumonia, most often the death occurs due to infection has reached the lungs. This condition is called sudden pneumonia or pneumonia. The number of pneumonia coverage in toddlers in West Sumatra Province is 10,576 cases, in the city of Padang in 2018 the estimated number of pneumonia sufferers is 3,196 children under five. The aim of community service is expected that mothers can manage Ispa / Pneumonia at home in Toddlers by using MTBS reading card media in the working area of Belimbing Public Health Center in Padang. The method of community service activities is simulation using MTBS reading card media, lectures, questions and answers, demonstrations, redemonstrations. The target activities of the Toddler Mother are 100 people. The results of the analysis show that the average value of the skills before using the media card is 9.04 and thereafter is 10.63. Wilcoxon test results p = 0.000 (p ≤ 0.05) which means that there is a significant increase in the skills of mothers of children under five in the management of ARI / pneumonia at home using MTBS reading card media. It is hoped that the sustainability of the program after the community service activities will be carried out in the form of similar activities and will continue to carry out continuous evaluations, taking into account the achievement of targets that must be achieved.